ANALISIS PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN (STUDI KASUS KOTA MEDAN) - Saraswati, Dwi; Putra Harahap, Ardhansyah (JURNAL PERPAJAKAN, 2025)
This study discusses the reception of Hotel Taxes and Restaurant Taxes in Medan. It is expected that research will provide benefits and input for the regional government of Medan City to the Regional Tax and Retribution Management Agency in Medan. The type of data taken is Qualitative data. The subjects in this study were the Office of the Regional Tax and Retribution Management in Medan. In this study the object of the research is the report on the hotel income tax and restaurant tax in Medan from 2016-2018. Data collection techniques were obtained by interview techniques and documentation. Data analysis techniques used in this study were descriptive qualitative methods, namely data obtained, analyzed, and interpreted so as to provide complete information. The results of research studies show that the Taxes for Hotel and Restaurant Taxes in Medan have considerable potential compared to other types of taxes. This is consistent with the purpose of the research, which is analyzing and explaining, the effectiveness of Hotel Taxes and Restaurant Taxes in Medan. The Hotel Tax contribution rate of 2.28% in 2016, in 2017 was 2.58% and in 2018 Hotel Tax was 2.18%. For the restaurant tax contribution of 3.11% in 2016, in 2017 it was 3.74% and in 2018 the restaurant tax contribution was 3.17%. Hotel Tax Effectiveness in Medan City is 9.60% in 2016, for 2017 at 8.53%, and in 2018 the Hotel Tax effectiveness is 9.83%. For the effectiveness of Restaurant Taxes in Medan at 9.60% in 2016, in 2017 it was 8.76%, and in 2018 the effectiveness of Restaurant Taxes in Medan was 9.98%.